Non-conventional Cascade Multilevel Inverter with Lower Number of Switches by Using Multilevel PWM - Abdali, Adala O.; Abdulabbas, Ali K.; Nekad, Habeeb J. (Iraqi Journal for Electrical and Electronic Engineering, 2021)
The multilevel inverter is attracting the specialist in medium and high voltage applications, among its types, the cascade H bridge Multi-Level Inverter (MLI), commonly used for high power and high voltage applications. The main advantage of the conventional cascade (MLI) is generated a large number of output voltage levels but it demands a large number of components that produce complexity in the control circuit, and high cost. Along these lines, this paper presents a brief about the non-conventional cascade multilevel topologies that can produce a high number of output voltage levels with the least components. The non-conventional cascade (MLI) in this paper was built to reduce the number of switches, simplify the circuit configuration, uncomplicated control, and minimize the system cost. Besides, it reduces THD and increases efficiency. Two topologies of non-conventional cascade MLI three phase, the Nine level and Seventeen level are presented. The PWM technique is used to control the switches. The simulation results show a better performance for both topologies. THD, the power loss and the efficiency of the two topologies are calculated and drawn to the different values of the Modulation index (ma).